ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH MELAKUKAN DEPOSITO MUDHARABAH PADA BANK SYARIAH DI KOTA PALOPO - Utami, Widya; Ramadhan, Abid; Sari, Harmita (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This study aims to determine the analysis of the factors that influence customers to make mudharabah deposits at Islamic banks in the city of Palopo. The data collection method used is direct questionnaires which are distributed directly to customers at Bank Muamalat Palopo City. The population in this study were all customers of Bank Muamalat Palopo City and the determination of the sample using the slovin formula technique with a total sample of 98 respondents. The data analysis technique used is multiple linear regression analysis. Based on the results of multiple linear regression analysis shows that the profit sharing ratio and promotion costs simultaneously have a significant effect on mudharabah deposits at Bank Muamalat Palopo City.